Comparison of UVC-based advanced oxidation processes in the mineralization of bisphenol A: Identi fication of oxidation by products and toxicity evaluation - Sanchez-Montes, Isaac; Wachter, Naihara; Silva, Bianca F. [UNESP]; Aquino, Jose M. (Elsevier B.V., 2020)
Water contamination by contaminants of emerging concern (CEC) represents a major challenge to our society regarding the need to assure a high quality drinking water to prevent humans from developing health problems. Thus, the performance of three different advanced oxidation processes (AOP: UVC/HOCl, UVC/S2O82-, and UVC/H2O2) based on the homolysis of oxidants were investigated for the oxidation and mineralization of bisphenol A (BPA) containing solutions as well as assessment of biotoxicity and identification of oxidation byproducts. In all AOP, UVC irradiation led to a significant improvement for the oxidation and mineralization of BPA due to the production of HO center dot/SO4 center dot- species. UVC/HOCl method was able to achieve high rates of conversion of BPA and its oxidation by-products to CO2. All detected oxidation by-products resulted from hydroxylation reactions. Considering the short chain carboxylic acids, mainly produced after opening the aromatic ring, high concentrations appeared mainly during the first two hours of treatment for the UVC/HOCl method with a complete elimination within 6 h of treatment, including the dichloroacetic acid. Biotoxicity assays using Artemia salina crustacean showed that the mortality was ceased after 4 h of treatment using the UVC/HOCl and UVC/S2O82- processes. In contrast, a low mortality decrease was observed when using the UVC/H2O2 process, probably due to the accumulation of toxic intermediates. In all scenarios, toxicity of the BPA compound and its oxidation by-products seem to be responsible for the distinct decays of mortality, as confirmed on the ECOSAR software. Finally, the UVC/HOCl method is an interesting option to eliminate CEC for removing levels attained and energy consumption.
Keywords: Plasticizers; Synthetic organic compounds; Hydroxylation reactions; Advanced oxidation processes; UVC irradiation; Synergistic e ffect